DnA_Design and Architecture – Cave di Jinyun, Zhejiang, Cina - Barbi, Simone (Firenze Architettura, 2023)
Il progetto alle cave di Jinyun espande la riflessione sulla agopuntura architettonica, avviata da Xu Tiantian e DnA_ Design and Architecture con la prolifica esperienza delle Songyang Stories, concentrandosi sulla risignificazione di spazi preesitenti, intervenendo con raffinati dettagli, ripetuti con ossessiva precisione, su un cluster di nove aule, differenti per dimensioni e vocazione d’uso, nel paesaggio estrattivo in abbandono della provincia di Zhejiang. The project at Jinyun Quarries broadens the reflection on architectural acupuncture, initiated by Xu Tiantian and DnA_ Design and Architecture with the fecund experience of the Songyang Stories, by focusing on the re-ascription of meaning of pre-existing spaces, intervening with refined details, repeated with obsessive precision, on a cluster of nine halls, different in size and intended usage, in the abandoned mining landscape of the province of Zhejiang.